2020
DOI: 10.3390/ijerph17228703
|View full text |Cite
|
Sign up to set email alerts
|

Projection of the Number of Elderly in Different Health States in Thailand in the Next Ten Years, 2020–2030

Abstract: The objective of this study is to predict the volume of the elderly in different health status categories in Thailand in the next ten years (2020–2030). Multistate modelling was performed. We defined four states of elderly patients (aged ≥ 60 years) according to four different levels of Activities of Daily Living (ADL): social group; home group; bedridden group; and dead group. The volume of newcomers was projected by trend extrapolation methods with exponential growth. The transition probabilities from one st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 8 publications
0
13
1
Order By: Relevance
“…This means that one out of every three Thais will be an older person [ 4 ]. The challenge of an aging population is coupled with the high prevalence and incidence of chronic non-communicable diseases (NCDs), such as hypertension, diabetes, stroke, and coronary artery diseases, which make older adults more vulnerable to disabilities that require special continuing care [ [5] , [6] , [7] ]. In Thailand, as in many low-to-middle-income countries in transition, failure to effectively implement evidence-informed intervention for older adults with chronic diseases represents a key obstacle in the progress of the healthcare system, resulting from the high burden of disease and the extreme shortage of human and material resources [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…This means that one out of every three Thais will be an older person [ 4 ]. The challenge of an aging population is coupled with the high prevalence and incidence of chronic non-communicable diseases (NCDs), such as hypertension, diabetes, stroke, and coronary artery diseases, which make older adults more vulnerable to disabilities that require special continuing care [ [5] , [6] , [7] ]. In Thailand, as in many low-to-middle-income countries in transition, failure to effectively implement evidence-informed intervention for older adults with chronic diseases represents a key obstacle in the progress of the healthcare system, resulting from the high burden of disease and the extreme shortage of human and material resources [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Globally, the number of older adults has continued to increase rapidly, from 1 billion in 2019 to an expected 1.4 billion by 2030 (World Health Organization, 2021 ). This trend is also evident in Thailand, where the population of individuals aged 60 years and older is 11.19 million in 2021 and is predicted to reach 15.59 million by 2030 (Tantirat et al, 2020 ). Hypertension is a medical condition that is highly prevalent in older adults and imposes major risk factors of heart disease, stroke, and renal failure.…”
Section: Introductionmentioning
confidence: 91%
“…Indeed, some 80–90% of elderly individuals have one chronic illness, and 50–77% have experienced a chronic illness more than twice [ 19 ]. Elderly Thais with chronic illness may be grouped as social, home, bedridden or dead [ 20 ]. In 2015, the Thai Ministry of Public Health reported that five million elderly patients, accounting for 21%, were living with chronic disease at home.…”
Section: Context and Theoretical Backgroundmentioning
confidence: 99%